Morphogenesis of the vulva and the vulval-uterine connection. - Gupta, Bhagwati P (WormBook, 2012)
The C. elegans hermaphrodite vulva is an established model system to study mechanisms of cell fate specification and tissue morphogenesis. The adult vulva is a tubular shaped organ composed of seven concentric toroids that arise from selective fusion between differentiated vulval progeny. The dorsal end of the vulval tubule is connected to the uterus via a multinucleate syncytium utse (uterine-seam) cell. The vulval tubule and utse are formed as a result of changes in morphogenetic processes such as cell polarity, adhesion, and invagination. A number of genes controlling these processes are conserved all the way up to human and function in similar developmental contexts. This makes it possible to extend the findings to other metazoan systems. Gene expression studies in the vulval and uterine cells have revealed the presence of regulatory networks specifying distinct cell fates. Thus, these two cell types serve as a good system to understand how gene networks confer unique cell identities both experimentally and computationally. This chapter focuses on morphogenetic processes during the formation of the vulva and its connection to uterus.